Primary Education: Barriers to Entry and Bottlenecks to Completion - Jose Ramon G. Albert; Clarissa C. David (Philippine Institute for Development Studies (PIDS), 2012)
To improve the country's standing on achieving the Millennium Development Goals on Education and Education for All targets, it is important to examine various economic and sociocultural demand-side factors that hinder children from attending and completing primary school, as well as maximizing their learning when they are in school. In this report, we look into two major issues regarding universal primary education, viz., late school entry and dropping out before completion of elementary, which are tied to a variety of factors related to demand for education. This paper focuses on a select few that appear to have substantial consequences on school attendance: perceptions about school readiness of children, economic factors (poverty and costs of education), differences in expectations between boys and girls, and education of mothers. Supply barriers also exacerbate these problems, particularly in a system that suffers continuous shortages of various education inputs. The examination in this paper includes reports using available national survey data and primary observations made during field visits and interviews in various areas of the country. This paper identifies and discusses the most pertinent factors related to why preprimary-aged children not in school are viewed as being too young for schooling, why primary-aged children not in school reportedly lack interest in schooling, and what puts some primary-aged students more at risk of dropping out than others.
Keywords: 330; poverty; Philippines; out-of-school children; dropouts; primary education; school readiness; gender disparities; input deficits; UN-Entwicklungsziele; Kinder; Allgemeinbildung; Schulbesuch; Dauer; Bildungschancen; Entwicklungsländer; Welt